1994
DOI: 10.1007/bf03009904
|View full text |Cite
|
Sign up to set email alerts
|

Awake intubation increases intracranial pressure without affecting cerebral blood flow velocity in infants

Abstract: Tracheal intubation is a necessary part of the anaesthetic management of many paediatric patients in the operating room. In adutts, the responses to laryngoscopy and tra-CAN J ANAESTH 1994 / 41:4 / pp281 7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
84
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 20 publications
0
84
0
Order By: Relevance
“…The MCA, the largest artery of all basal cerebral arteries constituting the Circle of Willis, is responsible for 70% of the blood flow to the ipsilateral hemisphere. 6 The advantage of recording CBFV from the MCA is that the M 1 segment of the MCA presents an angle < 20 ~ in relation to the temporal window which limits the effect on the Doppler shift by < 6% (cosine of the angle). A Medasonics CDS MP218 (Medasonics Inc., Fremont, Ca.)…”
Section: Methodsmentioning
confidence: 99%
“…The MCA, the largest artery of all basal cerebral arteries constituting the Circle of Willis, is responsible for 70% of the blood flow to the ipsilateral hemisphere. 6 The advantage of recording CBFV from the MCA is that the M 1 segment of the MCA presents an angle < 20 ~ in relation to the temporal window which limits the effect on the Doppler shift by < 6% (cosine of the angle). A Medasonics CDS MP218 (Medasonics Inc., Fremont, Ca.)…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] In addition to improving chances for successful intubation, paralytic agents are reported to attenuate adverse physiologic changes experienced during intubation attempts. Increased intracranial pressure, 2,3,26,27 increased systolic blood pressure 28 and longer duration of hypoxemia 10,29 have been reported in awake vs paralyzed neonatal intubations. The longterm consequences of these physiologic changes are not known.…”
Section: Common Practicesmentioning
confidence: 96%
“…In addition to causing discomfort, placing an endotracheal tube (ETT) without premedication is associated with adverse physiologic effects. These effects include bradycardia, 2,3 fluctuations in blood pressure (BP), [2][3][4][5][6][7][8] hypoxia, 2,3,7,[9][10][11] and increases in intracranial pressure (ICP). 3,4,6,8,12,13 Previous studies have shown that these potentially adverse effects can be attenuated by using pharmacologic agents.…”
mentioning
confidence: 99%